Bioluminescent Diagnostic Imaging to Characterize Altered Respiratory Tract Colonization by the Burkholderia Pseudomallei Capsule Mutant - Warawa, Jonathan M.; Long, Dan; Rosenke, Rebecca; Gardner, Don; Gherardini, Frank (Frontiers in Microbiology, 2011)
Pneumonia is a common manifestation of the highly fatal disease melioidosis, caused by the select agent bacteria Burkholderia pseudomallei. In this study we describe a new model system to investigate pulmonary melioidosis using bioluminescent-engineered bacteria in a murine respiratory disease model. Studies were performed to validate that the stable, light producing B. pseudomallei strain JW280 constitutively produced light in biologically relevant host-pathogen interactions. Hairless outbred SKH1 mice were used to enhance the ability to monitor B. pseudomallei respiratory disease, and were found to be similarly susceptible to respiratory melioidosis as BALB/c mice. This represents the first demonstration of in vivo diagnostic imaging of pulmonary melioidosis permitting the detection of B. pseudomallei less than 24 hours post infection. Diagnostic imaging of pulmonary melioidosis revealed distinct temporal patterns of bacterial colonization unique to both BALB/c and SKH1 mice. Validation of these model systems included the use of the previously characterized capsule mutant, which was found to colonize the upper respiratory tract at significantly higher levels than the wild- type strain. These model systems allow for high resolution detection of bacterial pulmonary disease which will facilitate studies of therapeutics and basic science evaluation of melioidosis.